THE LINGUO-COGNITIVE INTERPRETATION OF LANGUAGE AND THE ESSENCE OF COGNITIVE CATEGORIES - Nurmatova Sadbarxon Erkinovna (Ecomind Press, 2025)
This article analyzes the linguo-cognitive interpretation of language within the framework of modern cognitive linguistics. It substantiates the intrinsic relationship between language, human thinking, perception, and the processes of organizing and reconstructing knowledge. The essence of major cognitive categories—such as concept, mental model, and conceptual metaphor—is explored, and the function of language not only as a communicative tool but also as a mental system that structures the conceptual world model is explained. The research summarizes the contributions of scholars such as G. Lakoff, M. Johnson, R. Langacker, R. Jackendoff, A. Goldberg, and A. Wierzbicka to the development of cognitive approaches, along with studies conducted by Russian and Uzbek linguists. The findings show that language must be interpreted in close relation to cognitive, conceptual, and cultural contexts.
Keywords: Linguo-cognitive approach; cognitive linguistics; concept; mental model; conceptual metaphor; conceptosphere; cognitive meaning; language and thinking; cognitive grammar.